The enactment of ideology and self-presentation in political campaign videos of the 2015 general election in Nigeria. (April 2019) - Gbadegesin, Victoria Oluwamayowa; Onanuga, Paul Ayodele
Abstract: The nexus of power, ideology, and identity has been at the heart of linguistic enquiries into political discourse. The present study extends existing knowledge in its application of Multimodal Critical Discourse Analysis in studying six video advertisements of two major political parties during the 2015 Nigerian presidential elections. Focus was on the synergetic wielding of ideologies and identities as persuasive strategies by candidates and political parties. Analysing both verbal and non-verbal texts, we observe differences in the driving ideologies of the two parties. The Peoples' Democratic Party (PDP) anchors their campaigns on progressivism alongside two identities: progressivist and achiever identities. The All Progressives Congress' (APC) driving ideology is reformism, through which the reformist and rescuer identities are portrayed. While we assert that political parties convey discourse issues through multiple modes, these ideologies and identities are anchored towards creating long-lasting positive opinion in the electorate.